A eficiência dos sistemas de remuneração variável por desempenho no setor público brasileiro: estudo das experiências nos Estados de Minas Gerais, Ceará e Pará - Luis Claudio de Jesus Silva (2014)
The intensification of the social changes that occurred since the 70s, was crucial in transforming the way that the State was perceived and therefore the relations between state and society with the maximization has been demanding of public managers the search of management models not only capable of redefining structures as to make them more efficient. In this scenario, attract and keep people motivated, competitive and able to assist in maximizing organizational performance is one of the challenges to be overcome. To that end some Brazilian public organizations have implemented variable remuneration policies, guided by the previous setting goals and establishing rewards for improving the results. This research is focused on identifying the relationships between the systems of pay for performance and motivation and individual performance of Brazilian public servers under their perception. The survey consisted of descriptive/explanatory studies under a quantitative approach with conduction of fieldwork and data collection. The data collection was by selection and analysis of documents and the application of a structured questionnaire, available via intranet, to the public severs that work with the departments of Planning and management/Administration of the Brazilian states of Ceará, Minas Gerais and Pará. In all states, over 25% of the universe of serves fully completed the questionnaire. Data collected after grouped and tabulated, underwent quantitative analysis and statistical treatment, with results interpreted and compared with theory. Finally, the results indicate the efficiency of pay for performance program implanted in the surveyed public organizations. The programs influence the behavior of servers generating work motivation and this motivation has changed positively the individual performance. It was also possible to reap that the programs have the potential to alter positively the performance of the servers even when it do not generate motivation to work. The research reveals, the strategies adopted in some states and that deserve to be analyzed and the need for further studies to understand some phenomena that were also evident.